A N–H functionalized perylene diimide with strong red-light absorption for green solvent processed organic electronics. Issue 29 (22nd July 2020) - Harris, Dylan H.; Brixi, Samantha; Gelfand, Benjamin S.; Lessard, Benoît H.; Welch, Gregory C.
Abstract : The synthesis of a perylene diimide semiconductor using simple condensation chemistry that exhibits strong visible light absorption, green solvent solubility, and n-type charge mobility behavior. Abstract : The synthesis of a new perylene diimide organic semiconductor via the use of an acid-catalyzed condensation reaction is presented. The strategy involves the incorporation of an N–H moiety into the molecular design which can be polarized to facilitate green solvent processing. Compared to the parent chromophore, onset of optical absorption in solution is redshifted by 180 nm. Utility as an electron transporting semiconductor in organic field effect transistors is demonstrated.